How green was Portuguese colonialism? Agronomists and coffee in interwar Angola - Gago, Maria Do Mar (2018)
The origins of environmentalism are much older than we thought and the context of its emergence is far more complex than originally suggested. These are the two main conclusions of Richard Grove’s Green Imperialism: Colonial Expansion, Tropical Island Edens, and the Origins of Environmentalism, 1600- 1860 (Grove 1995). In this book, environmentalism appears not as a creation of the 20th century but firmly rooted in the 17th century. The argument of this English historian is simple: the experience of European imperialism, especially in island environments, was crucial in the development of conservationist notions and in the growing awareness of the limitability of local and global resources. This historiography of early environmentalism had important repercussions. Firstly, it forced us to gain distance from the environmental and political movements after World War ii and to investigate other reactions to human-induced ecological changes put forward in earlier times.1 Secondly, it compelled us to make a clear distinction between state and private sectors as far as imperial governance is concerned. As Grove insists, imperial states had a clear agenda as to why ruled territories should be environmentally sustainable, seeing this agenda as a guarantor of their longevity – in contrast with private capital and international trade-interests to which “global environmental wellbeing” was generally “an accounting irrelevance” (Grove 2002, 54).